Determining Bathymetry of Shallow and Ephemeral Desert Lakes Using Satellite Imagery and Altimetry. Issue 7 (8th April 2020) - Armon, M.; Dente, E.; Shmilovitz, Y.; Mushkin, A.; Cohen, T. J.; Morin, E.; Enzel, Y.
Abstract: Water volume estimates of shallow desert lakes are the basis for water balance calculations, important both for water resource management and paleohydrology/climatology. Water volumes are typically inferred from bathymetry mapping; however, being shallow, ephemeral, and remote, bathymetric surveys are scarce in such lakes. We propose a new, remote‐sensing‐based, method to derive the bathymetry of such lakes using the relation between water occurrence, during >30 year of optical satellite data, and accurate elevation measurements from the new Ice, Cloud, and Land Elevation Satellite‐2 (ICESat‐2). We demonstrate our method at three locations where we map bathymetries with ~0.3 m error. This method complements other remotely sensed, bathymetry‐mapping methods as it can be applied to: (a) complex lake systems with subbasins, (b) remote lakes with no in‐situ records, and (c) flooded lakes. The proposed method can be easily implemented in other shallow lakes as it builds on publically accessible global data sets. Plain Language Summary: Lakes in desert environments are often remote and shallow and only get filled once in a long while. They are an important water resource and could be used to decipher past environmental conditions. However, detailed maps of lake‐floor terrain, which are required to effectively study these lakes are typically not available. The deepest parts of the lakes are filled with water more frequently than their shallow margins. Thus, we suggest here to relate water occurrence in those lakes with accurate satellite‐based elevation measurements, to obtain a valuable lake‐floor terrain map. We demonstrate the usefulness of our method by comparing results with other globally available data. Previous methods struggle with complex‐terrain lakes or lakes that are partially flooded during their survey, while our method yields high‐resolution accurate maps even in such lakes. Key Points: A new methodology to produce bathymetry maps of shallow desert lakes was developed, based on globally available data sets The methodology enables mapping the bathymetry of lakes with subbasins or partially flooded lakes, both major limitations of other methods The derived bathymetry error is ~30 cm, rather than ~2.5 m for other globally available data